Synergistic integration of oxygen doping and a self-imprinted architecture in g-C3N4 for efficient and selective photocatalytic degradation of tetracycline - Xinyang Li; Yangrui Xu; Yipeng Liu; Yu Cheng; Liguang Tang; Hongping Li; Xinlin Liu; Hong Liu; Jie Jin; Ziyang Lu (Journal of Environmental Chemical Engineering, 2026)

Identification and formation pathways of oxidation products of chlorinated paraffins during ozonation in municipal wastewater - Enrui Li; Hongping Wang; Yibin Sun; Song Tang; Chao Wang; Yi Wan; Xudong Jia; Hong Chang (Journal of Environmental Sciences, 2026)

Multi-modal detection methods based on vortex fluid device mediated red-emitting carbon dots for sensitive vitamin B6 detection in food - Yanan Yan; Hongping Zhang; Youhong Tang; Xuan Luo; Colin L. Raston; Ruyu Li; Shaomin Shuang; Chuan Dong (Food Chemistry, 2026)

Editor's note to “Enhanced mechanistic insights and performance optimization: controlling methane and sulfide in sewers using nitrate dosing strategies” [Sci. Total Environ., 907 (2024) 167580] - Yan Chen; Yaxin Xing; Zhiqiang Zuo; Guangming Jiang; Hongping Min; Dingding Tang; Peng Liang; Xia Huang; Yanchen Liu (Science of The Total Environment, 2025)

NEDD4 facilitates the progression of endometrial carcinoma by enhancing PAMR1 protein degradation through ubiquitination - Hongbo Guo; Hongping Tang; Yihui Yang; Hui Xu; Jiaqi Fan; Shuxia Chen; Lingxiu Hou; Ying Yuan; Guangwu Zhang (Functional & Integrative Genomics, 2025)

Correction: Genetic dissection of flowering time and fine mapping of qFT.A02‑1 in rapeseed (Brassica napus L.) - Yanling Li; Xin Li; Dezhi Du; Qianru Ma; Zhi Zhao; Long Wang; Yongshun Zhang; Huiqin Shi; Hongping Zhao; Huaxin Li; Damei Pei; Zhigang Zhao; et al. (Theoretical and Applied Genetics, 2025)

Regulation CN reduction of CO2 products selectivity by adjusting the number of V sites and mechanism exploration - Zhi Zhu; Xiaohan Xing; Qi Qi; Hongping Li; Donglai Han; Xianghai Song; Xu Tang; Yun Hau Ng; Pengwei Huo (Fuel, 2025)

Genetic dissection of flowering time and fine mapping of qFT.A02-1 in rapeseed (Brassica napus L.) - Yanling Li; Xin Li; Dezhi Du; Qianru Ma; Zhi Zhao; Long Wang; Yongshun Zhang; Huiqin Shi; Hongping Zhao; Huaxin Li; Damei Pei; Zhigang Zhao; et al. (Theoretical and Applied Genetics, 2025)

Visualized generator for the simulation of wastewater quality and quantity variations in the sewer system - Yanchen Liu; Md Sahidul Islam; Jiale Chen; Mingkai Zhang; Hongping Min; Bo Li; Jianhua Mao; Dingding Tang; Moran Wang; Hanchang Shi; Xia Huang (Science of The Total Environment, 2024)

The adsorption behavior of perfluorooctane sulphonate on diamane regulated by strain - Hongping Zhang; Pengfei Tang; Shuchun Hu; Kun Yang; Ming Tang; Wei Feng; Qingyuan Wang; Haifei Zhan (Chemosphere, 2024)

A force-restricted inerter damper for enhancing the resilience of seismically isolated structures - Hongping Zhu; Zian Tang; Hao Luo; Shun Weng (Engineering Structures, 2024)

Effects of partial replacement of fishmeal with Spirulina platensis powder and addition of Spirulina platensis polysaccharide on growth, nutrition, antioxidant capacity and gut microbiota of Micropterus salmoides - Wenqi Zhang; Yongyan Deng; Zixin Yang; Qing Kong; Peiqin Liu; Hongping Liao; Huijuan Tang (Aquaculture, 2024)

Aralianudaside A, an unusual skeleton triterpenoid saponin with anti-airway inflammatory activity from Aralia elata - Pengcheng Yin; Haishan Qian; Shaohua Li; Benqin Tang; Juan Wang; Shuai Chen; Guanghui Ni; Fawu Dong; Yanping Li; Feng Huang; Rongping Zhang; Hongping He; et al. (Natural Product Research, 2024)

Nitrogen removal characteristics of novel bacterium Klebsiella sp. TSH15 by assimilatory/dissimilatory nitrate reduction and ammonia assimilation - Jilong Ren; Jiajun Tang; Hongping Min; Dingding Tang; Rui Jiang; Yanchen Liu; Xia Huang (Bioresource Technology, 2024)

Enhanced mechanistic insights and performance optimization: Controlling methane and sulfide in sewers using nitrate dosing strategies - Yan Chen; Yaxin Xing; Zhiqiang Zuo; Guangming Jiang; Hongping Min; Dingding Tang; Peng Liang; Xia Huang; Yanchen Liu (Science of The Total Environment, 2024)

High-performance isolation systems with rate-independent linear damping for seismic protection of high-rise buildings - Hao Luo; Zian Tang; Hongping Zhu (Soil Dynamics and Earthquake Engineering, 2023)

Microplastic Pollution and Its Potential Correlation with Environmental Factors in Daya Bay, South China Sea - Peiqin Liu; Hongping Liao; Yongyan Deng; Wenqi Zhang; Zhixi Zhou; Di Sun; Zhixin Ke; Aiguo Zhou; Huijuan Tang (Journal of Marine Science and Engineering, 2023)
Microplastics (MPs) have been given considerable attention due to their risk to aquatic organisms in marine environments. In this study, MPs’ abundance and their potential correlation with environmental factors were investigated from 26 sites in Daya Bay, South China Sea. The results showed that the abundance of MPs was 1.8–13.87 items/L in surface water and 190–823 items/kg (dry weight) in sediment. The most abundant shape of MPs in both water and sediment was fiber, the most abundant particle size was 0.5–1 mm and the most abundant color was transparent. In addition, the most common polymer type of MPs was polyethylene terephthalate (PET), followed by rayon (RY), polypropylene (PP), cellulose (CL) and polyethylene (PE). The abundance of MPs in sediment was significantly correlated with sediment organic N and C (p 0.05). A factor analysis showed that MPs in sediment might share similar sources with organic N and C, which were mainly from the autochthonous sedimentation of marine organisms, and MPs might sediment jointly with organic matter. In summary, this study reflects on MP pollution and the potential correlation with environmental factors, providing essential data for governmental agencies to formulate microplastic pollution control policies.

PAA/TiO2@C composite hydrogels with hierarchical pore structures as high efficiency adsorbents for heavy metal ions and organic dyes removal - Hongping Zhang; Pengfei Tang; Kun Yang; Qingyuan Wang; Wei Feng; Youhong Tang (Desalination, 2023)

Assessment of long-term functional maintenance of primary human hepatocytes to predict drug-induced hepatoxicity in vitro - Yi Chen; Dan Tang; Hongping Wu; Yuling Wu; Tianjie Yuan; Hongdan Zhang; Yingfu Jiao; Weifeng Yu; Hexin Yan (Archives of Toxicology, 2021)

Cell culture medium supplemented with taurine decreases basic charge variant levels of a monoclonal antibody - Mengjuan Liu; Jiaqi Wang; Hongping Tang; Li Fan; Liang Zhao; Hai-Bin Wang; Yan Zhou; Wen-Song Tan (Biotechnology Letters, 2018)

Chitooligosaccharide Inhibits Scar Formation and Enhances Functional Recovery in a Mouse Model of Sciatic Nerve Injury - Hongping Hou; Lihai Zhang; Zuguang Ye; Jianrong Li; Zijian Lian; Chao Chen; Rong He; Bo Peng; Qihua Xu; Guangping Zhang; Wenbiao Gan; Peifu Tang (Molecular Neurobiology, 2016)

Minocycline Attenuates Neonatal Germinal-Matrix-Hemorrhage-Induced Neuroinflammation and Brain Edema by Activating Cannabinoid Receptor 2 - Jun Tang; Qianwei Chen; Jing Guo; Liming Yang; Yihao Tao; Lin Li; Hongping Miao; Hua Feng; Zhi Chen; Gang Zhu (Molecular Neurobiology, 2016)

Differential miRNA expression in maize ear subjected to shading tolerance - Liuzheng Yuan; Jihua Tang; Jiayou Liu; Hang Song; Moubiao Zhang; Hongping Li; Chaohai Li (Acta Physiologiae Plantarum, 2016)

Culture temperature modulates monoclonal antibody charge variation distribution in Chinese hamster ovary cell cultures - Xintao Zhang; Ya-Ting Sun; Hongping Tang; Li Fan; Dongdong Hu; Jintao Liu; Xuping Liu; Wen-Song Tan (Biotechnology Letters, 2015)

Negative-Pressure Wound Therapy Enhances Local Inflammatory Responses in Acute Infected Soft-Tissue Wound - Daohong Liu; Lihai Zhang; Tongtong Li; Guoqi Wang; Hailong Du; Hongping Hou; Li Han; Peifu Tang (Cell Biochemistry and Biophysics, 2014)

Long-Term Treatment After Preoperative High-Dose Chemotherapy in a Lactating Breast Cancer Patient - Chengyun Yao; Hongping Xia; Yongsheng Wang; Jinhai Tang; Xiaobo Wang (Cell Biochemistry and Biophysics, 2014)

Erratum to: Autophagy Reduces Neuronal Damage and Promotes Locomotor Recovery via Inhibition of Apoptosis after Spinal Cord Injury in Rats - Peifu Tang; Hongping Hou; Licheng Zhang; Xia Lan; Zhi Mao; Daohong Liu; Chunqing He; Hailong Du; Lihai Zhang (Molecular Neurobiology, 2014)

Autophagy Reduces Neuronal Damage and Promotes Locomotor Recovery via Inhibition of Apoptosis After Spinal Cord Injury in Rats - Peifu Tang; Hongping Hou; Licheng Zhang; Xia Lan; Zhi Mao; Daohong Liu; Chunqing He; Hailong Du; Lihai Zhang (Molecular Neurobiology, 2014)

Precise orbit determination of Beidou Satellites with precise positioning - Chuang Shi; QiLe Zhao; Min Li; WeiMing Tang; ZhiGang Hu; YiDong Lou; HongPing Zhang; XiaoJi Niu; JingNan Liu (Science China Earth Sciences, 2012)

Grade classification of neuroepithelial tumors using high-resolution magic-angle spinning proton nuclear magnetic resonance spectroscopy and pattern recognition - WenXue Chen; HaiYan Lou; HongPing Zhang; Xiu Nie; WenXian Lan; YongXia Yang; Yun Xiang; JianPin Qi; Hao Lei; HuiRu Tang; FenEr Chen; Feng Deng (Science China Life Sciences, 2011)